A Noise Map of New York City - Wang, Yilun; Zheng, Yu; Liu, Tong (Proceedings of the 16th ACM International Conference on Ubiquitous Computing, 2014)
This demonstration presents a noise map of New York City, based on four ubiquitous data sources: 311 complaint data, social media, road networks, and Point of Interests (POIs). The noise situation of any location in the city, consisting of a noise pollution indicator and a noise composition, is derived through a context-aware tensor decomposition approach we proposed in [5]. Moreover, our demo highlights two components: a) ranking locations based on inferred noise indicators in various settings, e.g., on the weekdays (or weekends), in a time slot (or overall time), and in a noise category (or all categories); b) revealing the distribution of noises over different noise categories in a location. Related Conference Publication
A demo paper of UbiComp 2014